Environment-friendly sunlight-resistant sand-containing fog sealing layer and preparation method thereof

By adding environmentally friendly, sun-resistant microcapsules and other components to the asphalt mixture, an environmentally friendly, sun-resistant, sand-containing mist seal was prepared, which solved the problems of aging and flue gas release under the action of sunlight and high temperature, and achieved efficient maintenance and long-term service of the materials.

CN119859418AActive Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311360117.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The existing sand-containing mist sealing material cannot effectively solve the problems of asphalt pavement aging and flue gas release under the influence of sunlight and high temperature.

Method used

An environmentally friendly, sun-resistant, sand-containing mist sealing layer is adopted. By adding environmentally friendly, sun-resistant microcapsules, composite emulsifiers, defoaming agents, latex, suspension agents and fine sand particles to the asphalt mixture, a road surface maintenance material with ultraviolet resistance, temperature control and smoke suppression is formed.

Benefits of technology

Effectively reduce the aging degree and smoke release of asphalt pavement under high temperature sun exposure, extend the service time of asphalt pavement, and improve the wear resistance and embedded effect of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859418A_ABST
    Figure CN119859418A_ABST
Patent Text Reader

Abstract

The invention discloses an environment-friendly sunshine-resistant sand-containing fog sealing layer and a preparation method thereof. The environment-friendly sunshine-resistant sand-containing fog sealing layer disclosed by the invention comprises the following components in parts by mass: 35-95 parts of asphalt, 1-5 parts of a curing agent, 1-5 parts of a curing agent, 1-5 parts of a curing agent and 1-5 parts of a curing agent. 30 to 80 parts of water; 2-10 parts of a composite emulsifier; 0.5 to 3 parts of a defoaming agent; 10 to 50 parts of latex; 20 to 40 parts of a suspending agent; 20 to 45 parts of fine sand particles; 5 to 45 parts of environment-friendly sunlight-resistant microcapsules; the environment-friendly sunlight-resistant microcapsule comprises a shell material and a core material, the shell material is a composite shell material comprising titanium dioxide / nano tourmaline / polydopamine, the core material is n-alkane with the phase change temperature of 40-60 DEG C, and a metal chelate and a light stabilizer are loaded on the surface of the shell material. The environment-friendly sunshine-resistant sand-containing fog seal has good pavement performance, temperature control capability and anti-ultraviolet capability, and can inhibit the amount of pollutants generated by the asphalt pavement under the action of high temperature and solarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of special asphalt, and specifically relates to an environmentally friendly sunlight-resistant sand-containing fog seal layer and a preparation method thereof. Background Art

[0002] Asphalt pavement is the most common pavement type in China and even in the world. However, asphalt mixture, the material that makes up asphalt pavement, will not only crack and drop particles due to the combined effects of sunlight and high temperature during long-term service, but will also continuously release pollutants with pungent odors, ultimately greatly reducing the service life of asphalt pavement and endangering human health.

[0003] Sand-containing mist seal material is the most widely used pavement maintenance material at this stage. After being spread on the road surface, this type of material will soften the asphalt with poor adhesion and toughness on the surface layer, and at the same time repair the existing defects, thereby extending the service life of the road surface to a certain extent.

[0004] CN116285690A discloses a sand-containing mist seal material and a preparation method and application thereof. The method prepares a sand-containing mist seal material with high wear resistance and durability by controlling the types of polymer emulsion, filler and emulsified asphalt. However, the prepared sand-containing mist seal material can only be used for road maintenance after being spread on the road surface, and cannot solve the problem that asphalt is easily aged by sunlight and high temperature and releases irritating gases.

[0005] The sand-containing fog seal material produced by the prior art only considers repairing the existing road surface diseases, and does not consider the aging and smoke release problems caused by the road surface further exposed to sunlight and high temperature after the asphalt road surface is maintained. Therefore, it is very necessary to develop a road maintenance material that can effectively maintain the road surface while reducing the aging degree and smoke release of the asphalt road surface after being exposed to sunlight and high temperature. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides an environmentally friendly sunlight-resistant sand-containing fog seal and a preparation method thereof. The environmentally friendly sunlight-resistant sand-containing fog seal of the present invention not only has good road performance, temperature control ability and UV resistance, but also can effectively suppress the amount of pollutants generated by asphalt pavement under high temperature sunlight, providing a new idea for the functional utilization of asphalt materials.

[0007] The first aspect of the present invention provides an environmentally friendly sunlight-resistant sand-containing fog sealing layer, wherein the environmentally friendly sunlight-resistant sand-containing fog sealing layer comprises the following components in parts by mass:

[0008] Asphalt: 35-95 parts;

[0009] Water: 30-80 parts;

[0010] Composite emulsifier: 2-10 parts;

[0011] Defoaming agent: 0.5-3 parts;

[0012] Latex: 10-50 parts;

[0013] Suspension: 20-40 parts;

[0014] Fine sand: 20-45 parts;

[0015] Environmentally friendly sunlight-resistant microcapsules: 5-45 parts;

[0016] The environmentally friendly sunlight-resistant microcapsule comprises a shell material and a core material. The shell material is a composite shell material comprising titanium dioxide / nano-tourmaline / polydopamine. The core material is a normal alkane with a phase transition temperature of 40°C-60°C. The surface of the shell material is loaded with metal chelates and light stabilizers.

[0017] Furthermore, the asphalt is commercially available No. 70 or No. 90 base asphalt.

[0018] Furthermore, the composite emulsifier includes a cationic emulsifier and an amphoteric emulsifier, and the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.5.

[0019] Further, the cationic emulsifier includes one or more of amine salt type surfactants with a carbon number greater than 8; preferably one or more of tetradecyl-dimethylpyridinium ammonium bromide, octadecylamidopropyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amide propyl dimethyl dihydroxypropyl ammonium chloride, hexadecylamidopropyl trimethyl ammonium chloride, dioctadecyl-methylbenzyl ammonium chloride, dodecyl dimethylbenzyl ammonium chloride, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, and hexadecyl trimethyl ammonium chloride.

[0020] Furthermore, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters.

[0021] Furthermore, the defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol.

[0022] Furthermore, the latex is one or more of natural latex, carboxylated styrene-butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex.

[0023] Furthermore, the suspending agent is one or more of bentonite, kaolin, carbon black and talc.

[0024] Furthermore, the particle size of the suspending agent is 800-1800 mesh.

[0025] Furthermore, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.

[0026] Furthermore, the particle size of the fine sand particles is 30-300 mesh; preferably, the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%-60%, the mass proportion of sand particles of 70-130 mesh is 20%-30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%-30%.

[0027] Furthermore, the light stabilizer is selected from one or more of a benzophenone light stabilizer having more than 10 carbon atoms or a hindered amine light stabilizer having more than 15 carbon atoms.

[0028] Furthermore, the benzophenone-based light stabilizer having a carbon number greater than 10 is selected from one or more of BP-1 (2,4-dihydroxybenzophenone), BP-2 (2,2',4,4'-tetrahydroxybenzophenone), BP-3 (4-methoxy-2-hydroxybenzophenone), BP-4 (2-hydroxy-4-methoxy-5-sulfonic acid benzophenone), BP-8 (2,2'-hydroxy-4-methoxybenzophenone), and BP-12 (2-hydroxy-4-n-octyloxybenzophenone).

[0029] Furthermore, the hindered amine light stabilizer having a carbon number greater than 15 is selected from HALS-770 (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), HALS-292 (bis(1,2,2,6,6-pentamethylpiperidinol) sebacate), HALS-3346 (poly[(6-morpholinyl-1,3,5-triazine-2,4-yl)-((2,2,6,6-tetramethyl-4-piperidinyl)imino)hexane-((2,2,6,6-tetramethyl -4-piperidinyl)imino)]), HALS-944 (poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]), HALS-112 (bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate).

[0030] Furthermore, the particle size of the environmentally friendly sunlight-resistant microcapsules is 1-5 μm.

[0031] Furthermore, the mass ratio of the shell material to the core material of the environmentally friendly sunlight-resistant microcapsule is 1:(0.5-2).

[0032] Furthermore, the shell material of the modified sustained-release odor-free microcapsule is a composite shell material comprising titanium dioxide / nano-tourmaline / polydopamine, wherein the mass ratio of titanium dioxide to / nano-tourmaline is (1-5):1, and the mass ratio of titanium dioxide to polydopamine is 1:(0.1-0.5).

[0033] Furthermore, the surface of the shell material is loaded with a metal chelate, wherein the metal is preferably copper.

[0034] Furthermore, the shell material surface is loaded with metal chelate, and the metal loading accounts for 0.1wt%-15wt% of the total mass of the sustained-release odor-free microcapsule; the light stabilizer loading accounts for 0.1wt%-20wt% of the total mass of the odor-free temperature-controlling microcapsule.

[0035] Furthermore, the normal alkane with a phase transition temperature of 40°C-60°C is preferably one or more of n-octadecane, n-eicosane and n-docosane.

[0036] Furthermore, the method for preparing the environmentally friendly sunlight-resistant microcapsules comprises the following steps:

[0037] S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the nano-tourmaline under stirring, washing the nano-tourmaline after the modification, and freeze-drying the nano-tourmaline to obtain modified nano-tourmaline;

[0038] S2: heating the core material for later use;

[0039] S3: adding the solvent and the modified nano-tourmaline obtained in step S1 to the system in step S2, and stirring and mixing;

[0040] S4: adding a titanium dioxide precursor to the reaction system in step S3, stirring and mixing, and obtaining a Pickering emulsion;

[0041] S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 2-5, continuing stirring, then aging, filtering, and freeze-drying;

[0042] S6: adding the solid powder obtained in step S5 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying;

[0043] S7: adding the solid powder and the light stabilizer obtained in step S6 to an organic solvent, adding a strong base and reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying;

[0044] S8: adding the solid powder obtained in step S7 to the metal salt ion-formamide solution, treating under stirring, filtering, washing, and freeze-drying after the reaction is completed, to obtain environmentally friendly sunlight-resistant microcapsules.

[0045] Furthermore, in step S1, the diameter of the nano-tourmaline is 10-100 nm.

[0046] Furthermore, the surfactant in step S1 is a cationic surfactant, preferably one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride.

[0047] Furthermore, in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.

[0048] Furthermore, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (5-60):1.

[0049] Furthermore, in step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-200° C., and the modification time is 4-10 hours.

[0050] Furthermore, in step S1, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.

[0051] Furthermore, in step S2, the core material is heated to a temperature of 40-60°C.

[0052] Furthermore, in step S3, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.

[0053] Furthermore, in step S3, the mass ratio of the core material raw material to the modified nano-tourmaline is (1-20): 1. The mass ratio of the solvent to the modified nano-tourmaline is (10-80): 1.

[0054] Furthermore, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.

[0055] Furthermore, in step S4, the titanium dioxide precursor is one or more of n-butyl titanate, tetra-n-propyl titanate, and tetraethyl titanate.

[0056] Furthermore, in step S4, the mass ratio of the core material raw material to the titanium dioxide precursor is 1:(0.5-2).

[0057] Furthermore, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.

[0058] Furthermore, in step S5, the pH value can be adjusted by using dilute acid, such as dilute hydrochloric acid. The stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.

[0059] Furthermore, in step S5, the aging condition is: standing at 40-60°C for 12-30 hours. The freeze-drying condition is: vacuum drying at a temperature of -40--20°C for 4-8 hours.

[0060] Furthermore, in step S6, the buffer is one or more of phosphate buffer, carbonate buffer, and Tris buffer, preferably Tris buffer.

[0061] Furthermore, in step S6, the pH value of the buffer solution is 8-10.

[0062] Furthermore, in step S6, the mass ratio of the buffer solution to the solid powder obtained in step S5 is (30-200):1.

[0063] Furthermore, in step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.

[0064] Furthermore, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-30° C., and the stirring time is 12-24 hours.

[0065] Furthermore, in step S6, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.

[0066] Furthermore, in step S7, the strong base is one of solid KOH and solid NaOH, preferably solid KOH.

[0067] Furthermore, the organic solvent in step S7 is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol.

[0068] Furthermore, in step S7, the reaction temperature is 80-240° C., and the reaction time is 5-10 hours.

[0069] Furthermore, in step S7, the mass ratio of the solid powder to the organic solvent is 1:(20-100), the mass ratio of the solid powder to the light stabilizer is 1:(20-80), and the mass ratio of the solid powder to the strong base is 1:(0.5-4).

[0070] Furthermore, in step S7, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.

[0071] Further, in step S8, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate.

[0072] Furthermore, in step S8, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1.

[0073] Furthermore, the mass ratio of the metal ion salt-formamide solution in step S8 to the solid powder obtained in step S7 is (10-100):1.

[0074] Furthermore, in step S8, the stirring speed is 200-450 rpm, the stirring temperature is 100-190° C., and the stirring time is 2-5 hours.

[0075] Furthermore, in step S8, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.

[0076] The second aspect of the present invention provides a method for preparing the above-mentioned environmentally friendly sunlight-resistant sand-containing fog sealing layer, comprising the following steps:

[0077] P1: Preparation of composite emulsifier;

[0078] P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution;

[0079] P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt;

[0080] P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix;

[0081] P5: Add defoaming agent to the reaction system of step P4 and stir to mix;

[0082] P6: Add a suspending agent to the reaction system of step P5 and stir to mix;

[0083] P7: Add the environmentally friendly sunlight-resistant microcapsules to the reaction system of step P6 and stir to mix;

[0084] P8: Add the composite latex prepared in step P3 to the reaction system in step P7, and stir to mix;

[0085] P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an environmentally friendly sunlight-resistant sand-containing fog seal layer.

[0086] Furthermore, in step P1, the preparation of the composite emulsifier is to uniformly mix the cationic emulsifier and the amphoteric emulsifier.

[0087] Furthermore, in step P2, the water is preferably deionized. The mass ratio of the water to the composite emulsifier is: (5-20):1.

[0088] Furthermore, in step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes.

[0089] Furthermore, in step P2, the pH can be adjusted by using an acetic acid aqueous solution, and the pH value is adjusted to 2-4.

[0090] Furthermore, in step P3, the heating temperature of the asphalt is 113-183°C. The heating temperature of the soap solution is 30-60°C.

[0091] Furthermore, in step P3, the shearing is preferably performed multiple times, and more preferably 3-5 times. The shearing rate is 3000-5000 rpm each time, and the time of each shearing is 2-20 minutes.

[0092] Furthermore, in step P4, the mass ratio of the added composite emulsifier to the composite emulsifier added in step P2 is 1:2-5.

[0093] Furthermore, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.

[0094] Furthermore, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.

[0095] Furthermore, in step P6, the suspending agent is preferably added in multiple times, and more preferably added in 3-5 times.

[0096] Furthermore, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.

[0097] Furthermore, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.

[0098] Furthermore, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.

[0099] Furthermore, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.

[0100] Compared with the prior art, the present invention has the following advantages:

[0101] (1) The environmentally friendly sunlight-resistant microcapsules described in the present invention have nano-tourmaline in the composite shell material, which has three functions. The first function is that during the preparation process, the nano-tourmaline acts as a template for the synthesis of microcapsules and can maintain the stability of the precursor emulsion; the second function is that during the metal ion modification of the microcapsule composite shell material, a large amount of metal ions can be adsorbed onto the surface of the microcapsules with the help of the negative ion field released by the nano-tourmaline, effectively increasing the metal ion loading capacity of the microcapsule shell material and further improving the smoke suppression ability of the environmentally friendly sunlight-resistant microcapsules; the third function is that during the service of the road surface, after the environmentally friendly sunlight-resistant microcapsules are heated, the nano-tourmaline contained in the shell material will release a negative ion field, further attracting the compounds released by the asphalt road surface under the action of high temperature to the vicinity of the environmentally friendly sunlight-resistant microcapsules, while increasing the difficulty of these compounds to volatilize, and at the same time, the metal ions on the surface of the microcapsules can react with more of the above compounds, further inhibiting their volatilization, thereby effectively reducing the impact of the irritating gases released by the asphalt road surface on the human body.

[0102] (2) The environmentally friendly sunlight-resistant microcapsules of the present invention have a titanium dioxide shell material that can shield ultraviolet rays; the surface of the polydopamine shell material has a large number of active groups such as quinone groups and phenolic hydroxyl groups, and has good anti-ultraviolet ability. After the environmentally friendly sunlight-resistant sand-containing fog seal is spread on the road surface, the composite shell material of the environmentally friendly sunlight-resistant microcapsules contained therein can synergistically exert good anti-ultraviolet ability, effectively reducing the degree of ultraviolet aging during the service of the asphalt pavement.

[0103] (3) The environmentally friendly sunlight-resistant microcapsules of the present invention, with the help of a large number of active groups on the surface of the polydopamine shell layer, immobilize the light stabilizer on the surface of the microcapsules through Schiff base reaction and Michael addition reaction. After immobilization, the stability of the light stabilizer is greatly improved, effectively avoiding the loss of the light stabilizer due to heat, and having a long-lasting and efficient anti-ultraviolet ability.

[0104] (4) The light stabilizer immobilized on the shell surface of the environmentally friendly sunlight-resistant microcapsules of the present invention can not only effectively absorb ultraviolet rays with a wavelength of 290-410 nm, but also capture active free radicals generated by asphalt pavement under the action of ultraviolet rays. While effectively inhibiting the ultraviolet aging of asphalt, it can also reduce the generation of small molecular compounds in the asphalt system, thereby extending the service life of asphalt and reducing the impact of gas released from asphalt pavement on the environment.

[0105] (5) After the environmentally friendly sunlight-resistant sand-containing fog seal layer of the present invention is spread on the road surface, the core material of the environmentally friendly sunlight-resistant microcapsules contained therein can undergo phase change and absorb heat when the temperature of the asphalt road surface rises, thereby effectively reducing the temperature of the asphalt road surface. This can not only reduce the amount of gaseous small molecule compounds released by the asphalt road surface, but also effectively reduce the diseases of the asphalt road surface caused by high temperature, thereby extending the service life of the asphalt road surface.

[0106] (6) The environmentally friendly sunlight-resistant microcapsules of the present invention have an organic-inorganic multilayer composite shell material, which has high strength, is not easily broken, and has a long service life.

[0107] (7) After the environmentally friendly sunlight-resistant sand-containing fog seal layer of the present invention is spread on the road surface, the metal ions on the surface of the environmentally friendly sunlight-resistant microcapsule composite shell material in the system can react chemically with the small molecular compounds released by the asphalt road surface under high temperature, effectively reducing the malodorous gas released by the asphalt under the action of high temperature and sunlight, and avoiding the discomfort caused by the asphalt road surface to the human body.

[0108] (8) The environmentally friendly sunlight-resistant sand-containing fog seal layer of the present invention has an excellent embedding effect on the road surface and can effectively extend the service life of the road surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0109] Figure 1 This is an electron microscope image of the environmentally friendly sunlight-resistant microcapsules obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0110] To further illustrate the technical solution of the present invention, the present invention will be clearly and detailed described in conjunction with the embodiments below. It should be noted that the morphology test is performed by scanning electron microscopy, and the acceleration voltage used is 20 kV. Since the microcapsule wall material is not conductive, the sample needs to be treated with gold spraying before testing.

[0111] The smoke suppression effect of the environmentally friendly sunlight-resistant sand-containing fog seal layer of the present invention is tested by meteorological chromatography, and the test items are non-methane total hydrocarbons and sulfides.

[0112] Example 1

[0113] Preparation of environmentally friendly sunlight-resistant microcapsules:

[0114] S1: Add tourmaline with a diameter of 70 nm, hexadecyltrimethylammonium bromide and formamide into the first container in a mass ratio of 3:1:50, stir and react at 500 rpm and 190°C for 6 hours to modify the surface of the nano tourmaline, wash with ethanol several times after the reaction is completed, and vacuum dry at -30°C for 5 hours to obtain modified nano tourmaline for standby use;

[0115] S2: Add 5 parts by mass of n-docosane into the second container, and heat at 50° C. until it melts for later use;

[0116] S3: Add 50°C formamide and the modified nano-tourmaline obtained in step S1 to the above system, and stir at 50°C and 500 rpm for 5 hours, wherein the mass ratio of n-docosane, modified nano-tourmaline and formamide is 5:3:50;

[0117] S4: adding 5 parts by mass of tetraethyl titanate to the system of step S3, maintaining the rotation speed of 500 rpm and the temperature of 50° C., and continuing stirring for 4 hours to obtain a Pickering emulsion;

[0118] S5: maintaining the rotation speed of 500 rpm and the temperature of 50°C, slowly adding 10 wt% dilute hydrochloric acid to the system of step S4 using a peristaltic pump until the pH of the reaction system is 5, continuing stirring for 5 hours and then stopping stirring, maintaining the temperature and aging for 24 hours, then filtering and washing the solid powder in the reaction system, and vacuum drying at -30°C for 5 hours to obtain an environmentally friendly sunlight-resistant microcapsule precursor;

[0119] S6: 10 parts by weight of the environmentally friendly sunlight-resistant microcapsule precursor is added to 120 parts by weight of a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder is 80:1, and then dopamine hydrochloride is added to make the concentration of dopamine in the reaction system 5 mg / mL, and the mixture is stirred at 200 rpm for 12 hours at 25°C, and then the stirring is stopped. The bottom solid powder is filtered and washed, and then vacuum dried at a temperature of -30°C for 5 hours;

[0120] S7: adding the solid powder obtained in step S6 and the light stabilizers BP-1, BP-12 and HALS-112 in equal mass ratio to ethanol, further adding solid KOH, wherein the mass ratio of the solid powder obtained in step S6, the light stabilizer, methanol and solid KOH is 1:70:70:3, and refluxing for 10 hours at 90° C., then filtering and washing the bottom solid powder, and vacuum drying at -30° C. for 5 hours;

[0121] S8: Ultrasonic dispersion of the solid powder obtained in step S7 in a 50wt% anhydrous copper sulfate-formamide solution, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution being 1:70, stirring and reacting at 400 rpm and 140°C for 2 hours, filtering and washing the bottom solid powder after the reaction, and vacuum drying at -30°C for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules, the electron microscope image of which is as follows: Figure 1 .

[0122] The preparation method of environmentally friendly sunlight-resistant sand-fog seal is as follows:

[0123] P1: Add 2 parts by mass of hexadecyltrimethylammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;

[0124] P2: Add 55 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;

[0125] P3: Add 60 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C into a colloid mill, shear at a speed of 4000 rpm for 5 min, and cycle shear for 3 times to obtain emulsified asphalt;

[0126] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0127] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0128] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;

[0129] P7: Add 40 parts by weight of environmentally friendly sunlight-resistant microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;

[0130] P8: Add 13 parts by mass of carboxylated styrene butadiene latex and 17 parts by mass of chloroprene latex to the system of step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;

[0131] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of 30-70 mesh sand is 55%, the mass proportion of 70-130 mesh sand is 25%, and the mass proportion of 130-300 mesh sand is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an environmentally friendly, sunlight-resistant, sand-containing fog seal.

[0132] Example 2

[0133] Except that in step S7, the light stabilizers are BP-2, BP-3, and HALS-3346 in equal weight ratios, the rest is the same as in Example 1.

[0134] Example 3

[0135] Except that in step S7, the mass ratio of the solid powder, light stabilizer, methanol and KOH prepared in S6 is 1:65:70:3, the rest is the same as that in Example 1.

[0136] Example 4

[0137] Except that in step P8, the latex added is 13 parts by mass of natural latex and 17 parts by mass of nitrile latex, the rest is the same as Example 1.

[0138] Example 5

[0139] Except that in step P7, the amount of the environmentally friendly sunlight-resistant microcapsules used is 35 parts by mass, the rest is the same as in Example 1.

[0140] Example 6

[0141] Except for adding 6 parts by mass of carboxylated styrene butadiene latex and 8 parts by mass of chloroprene latex in step P8, the rest is the same as that in Example 1.

[0142] Example 7

[0143] Except that in step S3, the mass ratio of n-docosane, modified nano-tourmaline and formamide is 4:3:50, the rest is the same as that in Example 1.

[0144] Example 8

[0145] Except that in step S8, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:55, the rest is the same as that of Example 1.

[0146] Comparative Example 1

[0147] Preparation of environmentally friendly sunlight-resistant microcapsules:

[0148] Steps S1-S7 are the same as those in Embodiment 1, except that step S8 is omitted.

[0149] The preparation method of environmentally friendly sunlight-resistant sand-fog seal is as follows:

[0150] P1: Add 2 parts by mass of hexadecyltrimethylammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;

[0151] P2: Add 55 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;

[0152] P3: Add 60 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C into a colloid mill, shear at a speed of 4000 rpm for 5 min, and cycle shear for 3 times to obtain emulsified asphalt;

[0153] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0154] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0155] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;

[0156] P7: Add 40 parts by mass of the solid powder obtained in step S7 to the system of step P6, and stir and mix at 500 rpm and 60° C. for 50 minutes;

[0157] P8: Add 13 parts by mass of carboxylated styrene butadiene latex and 17 parts by mass of chloroprene latex to the system of step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;

[0158] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of 30-70 mesh sand is 55%, the mass proportion of 70-130 mesh sand is 25%, and the mass proportion of 130-300 mesh sand is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an environmentally friendly, sunlight-resistant, sand-containing fog seal.

[0159] Comparative Example 2

[0160] Preparation of environmentally friendly sunlight-resistant microcapsules:

[0161] S1: Add 5 parts by mass of n-docosane into a container and heat it at 50°C until it melts for later use;

[0162] S2: Add 50°C formamide and hexadecyltrimethylammonium bromide to the above system, stir at 50°C and 500 rpm for 5 hours, the mass ratio of n-docosane, hexadecyltrimethylammonium bromide and formamide is 5:3:50;

[0163] S3: adding 5 parts by mass of tetraethyl titanate to the system of step S2, maintaining the rotation speed of 500 rpm and the temperature of 50° C., and continuing stirring for 4 hours to obtain a Pickering emulsion;

[0164] S4: keeping the rotation speed at 500 rpm and the temperature at 50°C unchanged, using a peristaltic pump to slowly add 10 wt% dilute hydrochloric acid to the system in step S3 until the pH of the reaction system is 5, and then stopping stirring after continuing stirring for 5 hours, keeping the temperature unchanged and aging for 24 hours, then filtering and washing the solid powder in the reaction system, and vacuum drying at -30°C for 5 hours to obtain an environmentally friendly sunlight-resistant microcapsule precursor;

[0165] S5: 10 parts by weight of the environmentally friendly sunlight-resistant microcapsule precursor was added to 120 parts by weight of a Tris buffer solution with a pH of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder was 80:1, and then dopamine hydrochloride was added to make the concentration of dopamine in the reaction system 5 mg / mL. The mixture was stirred at 200 rpm for 12 hours at 25°C, and then the stirring was stopped. The bottom solid powder was filtered and washed, and then vacuum dried at -30°C for 5 hours.

[0166] S6: adding the solid powder obtained in step S5 and the light stabilizers BP-1, BP-12 and HALS-112 in equal mass ratio to ethanol, further adding KOH, wherein the mass ratio of the solid powder obtained in step S5, the light stabilizer, methanol and KOH is 1:70:70:3, and refluxing the mixture at 90°C for 10 hours, then filtering and washing the bottom solid powder, and vacuum drying the mixture at -30°C for 5 hours;

[0167] S7: ultrasonically dispersing the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:70, stirring and reacting at 400 rpm and 140° C. for 2 hours, filtering and washing the bottom solid powder after the reaction is completed, and vacuum drying at a temperature of -30° C. for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules;

[0168] The preparation method of the environmentally friendly sunlight-resistant sand-containing fog seal layer is the same as that of Example 1.

[0169] Comparative Example 3

[0170] Preparation of environmentally friendly sunlight-resistant microcapsules:

[0171] Steps S1-S6 are the same as in Example 1;

[0172] S7: ultrasonically dispersing the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:70, stirring and reacting at 400 rpm and 140° C. for 2 hours, filtering and washing the bottom solid powder after the reaction is completed, and vacuum drying at a temperature of -30° C. for 5 hours to obtain environmentally friendly sunlight-resistant microcapsules;

[0173] The preparation method of the environmentally friendly sunlight-resistant sand-containing fog seal layer is the same as that of Example 1.

[0174] Comparative Example 4

[0175] P1: Add 2 parts by mass of hexadecyltrimethylammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;

[0176] P2: Add 55 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;

[0177] P3: Add 60 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C into a colloid mill, shear at a speed of 4000 rpm for 5 min, and cycle shear for 3 times to obtain emulsified asphalt;

[0178] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0179] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0180] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;

[0181] P7: Add 13 parts by mass of carboxylated styrene butadiene latex and 17 parts by mass of chloroprene latex to the system of step P6, and stir and mix at 500 rpm and 60° C. for 40 minutes;

[0182] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of 30-70 mesh sand is 55%, the mass proportion of 70-130 mesh sand is 25%, and the mass proportion of 130-300 mesh sand is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an environmentally friendly, sunlight-resistant, sand-containing fog seal.

[0183] Comparative Example 5

[0184] Preparation of environmentally friendly sunlight-resistant microcapsules:

[0185] Steps S1-S5 are the same as those in Embodiment 1, except that steps S6-S8 are omitted.

[0186] The preparation method of environmentally friendly sunlight-resistant sand-fog seal is as follows:

[0187] P1: Add 2 parts by mass of hexadecyltrimethylammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;

[0188] P2: Add 55 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;

[0189] P3: Add 60 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C into a colloid mill, shear at a speed of 4000 rpm for 5 min, and cycle shear for 3 times to obtain emulsified asphalt;

[0190] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0191] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0192] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;

[0193] P7: Add 40 parts by weight of the environmentally friendly sunlight-resistant microcapsule precursor prepared in step S5 to the system of step P6, and stir and mix at 500 rpm and 60° C. for 50 minutes;

[0194] P8: Add 13 parts by mass of carboxylated styrene butadiene latex and 17 parts by mass of chloroprene latex to the system of step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;

[0195] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of 30-70 mesh sand is 55%, the mass proportion of 70-130 mesh sand is 25%, and the mass proportion of 130-300 mesh sand is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an environmentally friendly, sunlight-resistant, sand-containing fog seal.

[0196] Comparative Example 6

[0197] The preparation of environmentally friendly sunlight-resistant microcapsules is the same as in Example 1;

[0198] The preparation method of environmentally friendly sunlight-resistant sand-fog seal is as follows:

[0199] P1: Add 2 parts by mass of hexadecyltrimethylammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;

[0200] P2: Add 55 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;

[0201] P3: Add 60 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C into a colloid mill, shear at a speed of 4000 rpm for 5 min, and cycle shear for 3 times to obtain emulsified asphalt;

[0202] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0203] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;

[0204] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;

[0205] P7: Add 40 parts by weight of environmentally friendly sunlight-resistant microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;

[0206] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of 30-70 mesh sand is 55%, the mass proportion of 70-130 mesh sand is 25%, and the mass proportion of 130-300 mesh sand is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an environmentally friendly, sunlight-resistant, sand-containing fog seal.

[0207] Test Example 1

[0208] The wear of the environmentally friendly sunlight-resistant sand-fog sealing paint wheel and the bonding strength with the base surface were tested, and the obtained data are shown in Table 1 below.

[0209] Table 1 Environmentally friendly sunlight-resistant sand-fog seal performance test

[0210] sample <![CDATA[Wet wheel abrasion value / g·m -2 > 25℃ tensile strength / MPa Example 1 28.3 2.42 Example 2 28.6 2.40 Example 3 30.0 2.28 Example 4 28.9 2.37 Example 5 30.6 2.24 Example 6 31.7 2.16 Example 7 29.7 2.30 Example 8 29.4 2.33 Comparative Example 1 32.0 2.14 Comparative Example 2 32.5 2.10 Comparative Example 3 34.0 2.02 Comparative Example 4 35.4 1.94 Comparative Example 5 36.8 1.86 Comparative Example 6 67.4 1.33

[0211] Test Example 2

[0212] The gases released by asphalt pavement under the influence of high temperature are mainly volatile organic compounds and sulfides. In order to verify the smoke suppression ability of the insect-repellent and environmentally friendly sand-containing fog seal layer on asphalt materials of the present invention, the samples prepared in the embodiments and comparative examples are sprinkled on the surface of the asphalt mixture test block. The size of the asphalt mixture test block is 10cm*10cm*3cm. The samples are further moved into a sealed container with a gas intake port and stored at a temperature of 100°C for 1 day. After the storage is completed, the gas in the sealed container is absorbed, and the VOCs and H2S content in the gas are tested using a gas chromatograph. The obtained data are shown in Table 2 below.

[0213] Table 2 Asphalt smoke test data

[0214]

[0215]

[0216] Test Example 3

[0217] The UV aging test was carried out in a UV aging box with an UV intensity of 1200 μW / cm 2 The aging temperature is 60°C and the aging time is 20 days. The environmentally friendly sunlight-resistant fog seal layer prepared in the embodiment and the comparative example is spread on the surface of the rutting plate, and the dynamic stability of the obtained sample is tested after the aging is completed. The obtained data is shown in Table 3 below.

[0218] Table 3 Asphalt mixture dynamic stability test

[0219]

[0220]

[0221] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An environmentally friendly sunlight-resistant sand-containing fog seal, characterized by: The environmentally friendly sunlight-resistant sand-fog seal layer comprises the following components in parts by mass: Asphalt: 35-95 parts; Water: 30-80 parts; Composite emulsifier: 2-10 parts; Defoaming agent: 0.5-3 parts; Latex: 10-50 parts; Suspension: 20-40 parts; Fine sand: 20-45 parts; Environmentally friendly sunlight-resistant microcapsules: 5-45 parts; The environmentally friendly sunlight-resistant microcapsule comprises a shell material and a core material. The shell material is a composite shell material comprising titanium dioxide / nano-tourmaline / polydopamine. The core material is a normal alkane with a phase transition temperature of 40°C-60°C. The surface of the shell material is loaded with metal chelates and light stabilizers.

2. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The composite emulsifier includes a cationic emulsifier and an amphoteric emulsifier; the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.5; Preferably, the cationic emulsifier includes one or more of amine salt surfactants having a carbon number greater than 8; preferably one or more of tetradecyl-dimethylpyridinium ammonium bromide, octadecylamidopropyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amidopropyl dimethyl dihydroxypropyl ammonium chloride, hexadecylamidopropyl trimethyl ammonium chloride, dioctadecyl-methylbenzyl ammonium chloride, dodecyl dimethylbenzyl ammonium chloride, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, and hexadecyl trimethyl ammonium chloride; Preferably, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters.

3. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol; And / or, the latex is one or more of natural latex, carboxylated styrene butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex; And / or, the suspending agent is one or more of bentonite, kaolin, carbon black, and talc; And / or, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.

4. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The light stabilizer is selected from one or more of a benzophenone light stabilizer having a carbon number greater than 10 or a hindered amine light stabilizer having a carbon number greater than 15; Preferably, the benzophenone light stabilizer having a carbon number greater than 10 is selected from one or more of BP-1 (2,4-dihydroxybenzophenone), BP-2 (2,2',4,4'-tetrahydroxybenzophenone), BP-3 (4-methoxy-2-hydroxybenzophenone), BP-4 (2-hydroxy-4-methoxy-5-sulfonic acid benzophenone), BP-8 (2,2'-hydroxy-4-methoxybenzophenone), and BP-12 (2-hydroxy-4-n-octyloxybenzophenone); Preferably, the hindered amine light stabilizer having a carbon number greater than 15 is selected from HALS-770 (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), HALS-292 (bis(1,2,2,6,6-pentamethylpiperidinol) sebacate), HALS-3346 (poly[(6-morpholinyl-1,3,5-triazine-2,4-yl)-((2,2,6,6-tetramethyl-4-piperidinyl)imino)hexane-((2,2,6,6-tetramethyl -4-piperidinyl)imino)]), HALS-944 (poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]), HALS-112 (bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate).

5. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The particle size of the environmentally friendly sunlight-resistant microcapsules is 1-5 μm.

6. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The mass ratio of the shell material to the core material of the environmentally friendly sunlight-resistant microcapsule is 1:0.5-2.

7. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The shell material of the modified sustained-release odor-free microcapsule is a composite shell material comprising titanium dioxide / nano-tourmaline / polydopamine, wherein the mass ratio of titanium dioxide to / nano-tourmaline is 1-5:1, and the mass ratio of titanium dioxide to polydopamine is 1:0.1-0.

5.

8. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The surface of the shell material is loaded with metal chelate, wherein the metal is preferably copper; the metal loading accounts for 0.1wt%-15wt% of the total mass of the sustained-release odor-free microcapsule; the light stabilizer loading accounts for 0.1wt%-20wt% of the total mass of the odor-free temperature-controlling microcapsule.

9. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The normal alkane with a phase transition temperature of 40° C.-60° C. is preferably one or more of n-octadecane, n-eicosane, and n-docosane.

10. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 1, characterized in that: The method for preparing the environmentally friendly sunlight-resistant microcapsules comprises the following steps: S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the nano-tourmaline under stirring, washing the nano-tourmaline after the modification, and freeze-drying the nano-tourmaline to obtain modified nano-tourmaline; S2: heating the core material for later use; S3: adding the solvent and the modified nano-tourmaline obtained in step S1 to the system in step S2, and stirring and mixing; S4: adding a titanium dioxide precursor to the reaction system in step S3, stirring and mixing, and obtaining a Pickering emulsion; S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 2-5, continuing stirring, then aging, filtering, and freeze-drying; S6: adding the solid powder obtained in step S5 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying; S7: adding the solid powder and the light stabilizer obtained in step S6 to an organic solvent, adding a strong base and reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying; S8: adding the solid powder obtained in step S7 to the metal salt ion-formamide solution, treating under stirring, filtering, washing, and freeze-drying after the reaction is completed, to obtain environmentally friendly sunlight-resistant microcapsules.

11. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: The surfactant in step S1 is a cationic surfactant, preferably one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride; in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, in step S1, the mass ratio of the nano-tourmaline to the surfactant is 1-10:1, and the mass ratio of the solvent to the surfactant is 5-60:

1.

12. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-200° C., and the modification time is 4-10 hours; And / or, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S5, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours; And / or, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-30° C., and the stirring time is 12-24 hours; And / or, in step S8, the stirring speed is 200-450 rpm, the stirring temperature is 100-190° C., and the stirring time is 2-5 hours.

13. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S3, the solvent is an aprotic solvent with a boiling point > 100°C, preferably one or more of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; in step S3, the mass ratio of the core material to the modified nano-tourmaline is 1-20:

1. The mass ratio of the solvent to the modified nano-tourmaline is 10-80:

1.

14. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S4, the titanium dioxide precursor is one or more of n-butyl titanate, tetra-n-propyl titanate, and tetraethyl titanate; in step S4, the mass ratio of the core material raw material to the titanium dioxide precursor is 1:0.5-2.

15. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S6, the buffer is one or more of phosphate buffer, carbonate buffer, and tris(hydroxymethylaminomethane) hydrochloride buffer, preferably tris(hydroxymethylaminomethane) hydrochloride buffer; the pH value of the buffer is 8-10; in step S6, the mass ratio of the buffer to the solid powder obtained in step S5 is 30-200:

1.

16. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.

17. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: The organic solvent in step S7 is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol; And / or, in step S7, the reaction temperature is 80-240° C., and the reaction time is 5-10 hours; And / or, in step S7, the mass ratio of the solid powder to the organic solvent is 1:20-100, the mass ratio of the solid powder to the light stabilizer is 1:20-80, and the mass ratio of the solid powder to the strong base is 1:0.5-4.

18. The environmentally friendly sunlight-resistant sand-containing fog seal layer according to claim 10, characterized in that: In step S8, the mass ratio of the metal ion salt to formamide in the metal ion salt-formamide solution is 0.5-1.5:1; the mass ratio of the metal ion salt-formamide solution in step S8 to the solid powder obtained in step S7 is 10-100:

1.

19. A method for preparing an environmentally friendly sunlight-resistant sand-containing fog seal according to any one of claims 1 to 18, characterized in that: The steps include: P1: Preparation of composite emulsifier; P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution; P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt; P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix; P5: Add defoaming agent to the reaction system of step P4 and stir to mix; P6: Add a suspending agent to the reaction system of step P5 and stir to mix; P7: Add the environmentally friendly sunlight-resistant microcapsules to the reaction system of step P6 and stir to mix; P8: Add the composite latex prepared in step P3 to the reaction system in step P7, and stir to mix; P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an environmentally friendly sunlight-resistant sand-containing fog seal layer.

20. The preparation method according to claim 19, characterized in that: In step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes; And / or, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.

21. The preparation method according to claim 19, characterized in that: In step P2, the pH is adjusted by using an acetic acid aqueous solution, and the pH value is adjusted to 2-4.

22. The preparation method according to claim 19, characterized in that: In step P4, the mass ratio of the added composite emulsifier to the composite emulsifier added in step P2 is 1:2-5.

Citation Information

Patent Citations

  • Sand-containing fog seal material as well as preparation method and application thereof

    CN116285690A

  • Preparation method of fog sealing layer recycled material

    CN111534113A

  • Sand-containing fog seal mixture and application thereof

    CN115584209A

  • Anti-freezing sand-containing fog seal material and preparation method thereof

    CN116253533A

  • Asphalt restoration agent microcapsule and preparation method and use thereof

    US10357752B1